A systematic review on the management of pruritus in patients with cutaneous T-cell lymphoma. Issue 2 (April 2021) - Farrah, Georgia; Spruijt, Odette; McCormack, Chris; Buelens, Odette; Lazarakis, Smaro; Prince, Miles
Abstract : Introduction: Cutaneous T-cell lymphomas (CTCLs) represent a rare group of primary cutaneous lymphomas. Pruritus is common in patients with CTCL and is severe and intractable in the subtypes Sézary syndrome (SS) and folliculotropic mycosis fungoides (MF). Materials and methods: We conducted a systematic review on interventions demonstrating efficacy in reducing pruritus in patients with CTCL. The primary aim of our study was to identify disease-directed and itch-directed therapies effective in reducing CTCL-associated pruritus. Our secondary aim was to outline various tools used to quantify itch in clinical studies. Results: Our study identified multiple disease-directed therapies effective in reducing CTCL-associated pruritus. Most evidence supported the use of histone deacetylase inhibitors. For the agents romidepsin, vorinostat, and quisinostat, reduction in pruritus was achieved in both disease responders and nonresponders. Various therapies were effective in managing pruritus associated with SS and folliculotropic MF. Vorinostat is effective in reducing pruritus in patients with SS. Extracorporeal photophoresis, total skin electron beam therapy, and romidepsin are effective in reducing pruritus in patients with folliculotropic MF. The antiemetic aprepitant is an effective targeted treatment of CTCL-associated pruritus. Aprepitant demonstrated efficacy in reducing pruritus in patients with all stages of MF, including patients with SS. Lignocaine administered via continuous subcutaneous infusion is effective in reducing pruritus in patients with advanced-stage MF, including patients with SS. The most frequently used tools to quantify itch were the Visual Analogue Scale and Numerical Rating Scale. Definitions of a significant reduction in pruritus were extremely varied between studies. Discussion: To our knowledge, this is the first systematic review specifically addressing the management of itch in patients with CTCL. Patients with all stages of CTCL were represented across included studies, including patients with folliculotropic MF and SS. A wide range of treatment options were identified, including options appropriate for patients with end-stage disease.